(x-2)3+6(x+1)2-x3+12=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
e, \(\left(x-2\right)\left(x+2\right)+\left(x-2\right)^2=0\Leftrightarrow\left(x-2\right)\left(x+2+x-2\right)=0\Leftrightarrow x=0;x=2\)
f, \(\left(x+1\right)\left(x^2-x+1\right)-x\left(x+1\right)=0\Leftrightarrow\left(x+1\right)\left(x-1\right)^2=0\Leftrightarrow x=1;x=-1\)
g, \(x^2\left(x-3\right)+4\left(3-x\right)=0\Leftrightarrow\left(x-2\right)\left(x+2\right)\left(x-3\right)=0\Leftrightarrow x=2;x=-2;x=3\)
h, \(\left(2x-1-x-3\right)\left(2x-1+x+3\right)=0\Leftrightarrow\left(x-4\right)\left(3x+2\right)=0\Leftrightarrow x=4;x=-\dfrac{2}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1)
a)\(0,\left(32\right)+0,\left(67\right)\)
\(=0,\left(01\right).32+0,\left(01\right).67\)
\(=0,\left(01\right).\left(32+67\right)\)
\(=\frac{1}{99}.99\)
\(=1\left(đpcm\right)\)
b)\(0,\left(33\right).3\)
\(=0,\left(01\right).33.3\)
\(=\frac{1}{99}.33.3\)
\(=\frac{33}{99}.3\)
\(=\frac{99}{99}\)
\(=1\left(đpcm\right)\)
2)\(0,\left(12\right):1,\left(6\right)=x:0,\left(3\right)\)
\(\left[\left(0,01\right).12\right]:\left[1+0,\left(6\right)\right]=x:\left[0,\left(1\right).3\right]\)
\(\left(\frac{1}{99}.12\right):\left[1+0,\left(1\right).6\right]=x:\left(\frac{1}{9}.3\right)\)
\(\frac{4}{33}:\left[1+\frac{1}{9}.6\right]=x:\frac{1}{3}\)
\(\frac{4}{33}:\left[1+\frac{2}{3}\right]=x.3\)
\(3x=\frac{4}{33}:\frac{5}{3}\)
\(3x=\frac{4}{33}\cdot\frac{3}{5}\)
\(3x=\frac{4}{55}\)
\(x=\frac{4}{55}:3\)
\(x=\frac{4}{55}\cdot\frac{1}{3}\)
\(x=\frac{4}{165}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,PT\Leftrightarrow x^3-6x^2+12x-8-x^3+x+6x^2-18x-10=0\)
\(\Leftrightarrow-5x-18=0\)
\(\Leftrightarrow x=-\dfrac{18}{5}\)
Vậy ...
\(b,PT\Leftrightarrow x^3+3x^2+3x+1-x^3+3x^2-3x+1-6x^2+12x-6+10=0\)
\(\Leftrightarrow12x+6=0\)
\(\Leftrightarrow x=-\dfrac{1}{2}\)
Vậy ...
\(c,PT\Leftrightarrow\left(x+1\right)^3+3^3=0\)
\(\Leftrightarrow\left(x+1+3\right)\left(x^2+2x+1-3x-3+9\right)=0\)
\(\Leftrightarrow\left(x+4\right)\left(x^2-x+7\right)=0\)
Thấy : \(x^2-\dfrac{2.x.1}{2}+\dfrac{1}{4}+\dfrac{27}{4}=\left(x-\dfrac{1}{2}\right)^2+\dfrac{27}{4}\ge\dfrac{27}{4}>0\)
\(\Rightarrow x+4=0\)
\(\Leftrightarrow x=-4\)
Vậy ...
\(d,PT\Leftrightarrow\left(x-2\right)^3+1^3=0\)
\(\Leftrightarrow\left(x-2+1\right)\left(x^2-4x+4-x+2+1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-5x+7\right)=0\)
Thấy : \(x^2-5x+7=x^2-\dfrac{5.x.2}{2}+\dfrac{25}{4}+\dfrac{3}{4}=\left(x-\dfrac{5}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}>0\)
\(\Rightarrow x-1=0\)
\(\Leftrightarrow x=1\)
Vậy ...
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\Leftrightarrow x^3-8-x^3-2x=12\Leftrightarrow-2x=20\Leftrightarrow x=-10\\ b,\Leftrightarrow x^2-6x+9-x^2+4=16\Leftrightarrow=-6x=3\Leftrightarrow x=-\dfrac{1}{2}\\ c,\Leftrightarrow x\left(x^2-9\right)=0\\ \Leftrightarrow x\left(x-3\right)\left(x+3\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\\x=-3\end{matrix}\right.\\ d,\Leftrightarrow x^2\left(x-6\right)+9\left(x-6\right)=0\\ \Leftrightarrow\left(x^2+9\right)\left(x-6\right)=0\\ \Leftrightarrow x=6\left(x^2+9>0\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. (3x - 1)2 - (x + 3)2 = 0
\(\Leftrightarrow\left(3x-1+x+3\right)\left(3x-1-x-3\right)=0\)
\(\Leftrightarrow\left(4x+2\right)\left(2x-4\right)=0\)
\(\Leftrightarrow4x+2=0\) hoặc \(2x-4=0\)
1. \(4x+2=0\Leftrightarrow4x=-2\Leftrightarrow x=-\dfrac{1}{2}\)
2. \(2x-4=0\Leftrightarrow2x=4\Leftrightarrow x=2\)
S=\(\left\{-\dfrac{1}{2};2\right\}\)
b. \(x^3=\dfrac{x}{49}\)
\(\Leftrightarrow49x^3=x\)
\(\Leftrightarrow49x^3-x=0\)
\(\Leftrightarrow x\left(49x^2-1\right)=0\)
\(\Leftrightarrow x\left(7x+1\right)\left(7x-1\right)=0\)
\(\Leftrightarrow x=0\) hoặc \(7x+1=0\) hoặc \(7x-1=0\)
1. x=0
2. \(7x+1=0\Leftrightarrow7x=-1\Leftrightarrow x=-\dfrac{1}{7}\)
3. \(7x-1=0\Leftrightarrow7x=1\Leftrightarrow x=\dfrac{1}{7}\)
\(\left(x-2\right)^3+6\left(x+1\right)^2-x^3+12=0\)
<=> \(x^3-6x^2+12x-8+6\left(x^2+2x+1\right)-x^3+12=0\)
<=> \(24x+10=0\)
<=> \(24x=-10\)
<=> \(x=-\frac{5}{12}\)
Vậy...